Everolimus Versus Mycophenolate Mofetil in Heart Transplantation: A Randomized, Multicenter Trial. Issue 5 (22nd February 2013) - Eisen, H. J.; Kobashigawa, J.; Starling, R. C.; Pauly, D. F.; Kfoury, A.; Ross, H.; Wang, S.‐S.; Cantin, B.; Van Bakel, A.; Ewald, G.; Hirt, S.; Lehmkuhl, H.; et al.
<x xml:space="preserve">Abstract</x> In an open‐label, 24‐month trial, 721 de novo heart transplant recipients were randomized to everolimus 1.5 mg or 3.0 mg with reduced‐dose cyclosporine, or mycophenolate mofetil (MMF) 3 g/day with standard‐dose cyclosporine (plus corticosteroids ± induction). Primary efficacy endpoint was the 12‐month composite incidence of biopsy‐proven acute rejection, acute rejection associated with hemodynamic compromise, graft loss/retransplant, death or loss to follow‐up. Everolimus 1.5 mg was noninferior to MMF for this endpoint at month 12 (35.1% vs. 33.6%; difference 1.5% [97.5% CI: –7.5%, 10.6%]) and month 24. Mortality to month 3 was higher with everolimus 1.5 mg versus MMF in patients receiving rabbit antithymocyte globulin (rATG) induction, mainly due to infection, but 24‐month mortality was similar (everolimus 1.5 mg 10.6% [30/282], MMF 9.2% [25/271]). Everolimus 3.0 mg was terminated prematurely due to higher mortality. The mean (SD) 12‐month increase in maximal intimal thickness was 0.03 (0.05) mm with everolimus 1.5 mg versus 0.07 (0.11) mm with MMF (p < 0.001). Everolimus 1.5 mg was inferior to MMF for renal function but comparable in patients achieving predefined reduced cyclosporine trough concentrations. Nonfatal serious adverse events were more frequent with everolimus 1.5 mg versus MMF. Everolimus 1.5 mg with reduced‐dose cyclosporine offers similar efficacy to MMF with standard‐dose cyclosporine and reduces intimal proliferation at 12 months in de novo heart transplant recipients.